ANALISYS OF THERMAL EFFICIENCY OF A MODIFIED SOLAR COLLECTOR TYPE EVACUATED TUBE - Avallone, E.; Sato, A. I.; Scalon, V. L.; Padilha, A. (Revista de Engenharia Térmica, 2014)
The need of renewable energy sources due to climate change and thus the search for clean energy sources, justify the growing investment on new types of solar collectors. The research has contributed to this expansion in the scope of solar concentrator collectors, with the efficiency as the main goal. Many works have been developed in order to optimize the thermal stratification of the fluid inside the tubes and heat reservoirs, as well as mathematical modeling considering the problem as transient heat flow as boundary condition. In this work is studied experimentally, the heating of the water by solar collector modified from the conventional evacuated tube, focusing on efficiency. With the help of CFD software, a theoretical analysis is done to visualize the phenomenon, assuming the same boundary conditions and geometric experimental problem. An important approach concerns the physical separation of the flows of both cold and hot water inside the evacuated tube. The system performance was analyzed using experimental tests performed outdoors with sunlight.